HIGH-RESOLUTION PALEOPRODUCTIVITY FLUCTUATIONS DURING THE PAST 24 KYR AS INDICATED BY BENTHIC FORAMINIFERA IN THE MARGINAL ARCTIC OCEAN - Wollenburg J.E.; Mackensen A.; Knies J. (My University, 2004)
Analyses of benthic foraminifera in sediment cores taken at about 1000 m water depth at the Yermak Plateau and the Barents Sea slope, adjacent to the position of the ice-sheet edge during the Last Glacial Maximum, show that paleoproductivity was reduced to about a third of its present level during peak glacial stadials. These reduced values are still higher than values for modern, permanently ice-covered regions, suggesting that the core locations were at least partially ice-free even during stadials. Paleoproductivity at the core locations was higher than or equal to that of today during initial deglaciations and warm substages. Peak paleoproductivity occurred in samples with low-salinity surface waters as indicated by oxygen isotope values of planktonic foraminifera, and slightly after increased abundance of ‘Atlantic species’, suggesting that enhanced advection of warmer waters from the Atlantic supported the initial ice-sheet retreat. During the Holocene Climatic Optimum productivity was much less than at present on the Yermak Plateau, high at the Barents Sea site, perhaps because of increased advection of Atlantic water to the latter site and heavier ice coverage at the former. After this optimum, paleoproductivity at both sites was similar, with slightly lower values during cold periods such as the Little Ice Age.
Keywords: foraminifera; productivity; Arctic Ocean; Weichselian; deglaciation; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен